Reference genome provide insights into sex determination of silver aworana (Osteoglossum bicirrhosum) - Yi Liu; Chao Bian; Ka Yan Ma; Yexin Yang; Yuanyuan Wang; Chao Liu; Guochang Ouyang; Meng Xu; Jinhui Sun; Changwei Shao; Jiehu Chen; Qiong Shi; et al. (BMC Biology)
Abstract Background Silver arowana (Osteoglossum bicirrhosum) is a basal fish species with sexual monomorphism, while its sex determination mechanism has been poorly understood, posing a significant challenge to its captive breeding efforts. Results We constructed two high-quality chromosome-level genome assemblies for both female and male silver arowana, with scaffold N50 values over 10 Mb. Combining re-sequencing data of 109 individuals, we identified a female-specific region, which was localized in a non-coding region, i.e., around 26-kb upstream of foxl2 gene (encoding forkhead box L2). Its strong interaction with the neighboring foxl2 on the same chromosome suggests foxl2 as a candidate sex-related gene in silver arowana. We subsequently propose a complex gene network in the sex determination process of silver arowana, with foxl2 acting as the central contributor. Transcriptome sequencing of gonads support our hypothesis that the regulation of foxl2 can be influenced by the spatial proximity of the female-specific fragment, thereby promoting ovarian function or inhibiting testicular function to stimulate gonadal differentiation. Furthermore, we found the sex chromosomes to be homomorphic with a potentially recent origin, as a linkage disequilibrium analysis proved minor recombination suppression. Conclusions These results taken together serve as a crucial foundation for conducting extensive investigations on the evolution and differentiation of sex-determining mechanisms, as well as the emergence and development of sex chromosomes in various fishes.